EWSR1, a multifunctional protein, regulates cellular function and aging via genetic and epigenetic pathways - Lee, Junghee (Biochim Biophys Acta Mol Basis Dis, 2018)
Ewing’s sarcoma (EWS) is a bone cancer arising predominantly in young children. EWSR1 (Ewing Sarcoma breakpoint region 1/EWS RNA binding protein 1) gene is ubiquitously expressed in most cell types, indicating it has diverse roles in various cellular processes and organ development. Recently, several studies have shown that missense mutations of EWSR1 genes are known to be associated with central nervous system disorders such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Otherwise, EWSR1 plays epigenetic roles in gene expression, RNA processing, and cellular signal transduction. Interestingly, EWSR1 controls micro RNA (miRNA) levels via Drosha, leading to autophagy dysfunction and impaired dermal development. Ewsr1 deficiency also leads to premature senescence of blood cells and gamete cells with a high rate of apoptosis due to the abnormal meiosis. Despite these roles of EWSR1 in various cellular functions, the exact mechanisms are not yet understood. In this context, the current review overviews a large body of evidence and discusses on what EWSR1 genetic mutations are associated with brain diseases and on how EWSR1 modulates cellular function via the epigenetic pathway. This will provide a better understanding of bona fide roles of EWSR1 in aging and its association with brain disorders.